An Adaptive and Hybrid End-Point/Joint Impedance Controller for Lower Limb Exoskeletons - Maggioni, Serena; Reinert, Nils; Lünenburger, Lars; Melendez-Calderon, Alejandro (Frontiers in Robotics and AI, 2018)
Assist-as-needed (AAN) algorithms for the control of lower extremity rehabilitation robots can promote active participation of the patients during training while adapting to the individual performances and impairments. The implementation of such controllers requires the adaptation of a control parameter (often the robot impedance) based on a performance (or error) metric. The choice of how an adaptive impedance controller is formulated implies different challenges and possibilities for controlling the patient’s leg movement. In this paper, we analyze the characteristics and limitations of controllers defined in two commonly used formulations: joint and end-point space, exploring especially the implementation of an AAN algorithm. We propose then, as a proof-of-concept, an AAN impedance controller that combines the strengths of working in both spaces: a hybrid joint/end-point impedance controller. This approach gives the possibility to adapt the end-point stiffness in magnitude and direction in order to provide a support that targets the kinematic deviations of the end-point with the appropriate force vector. This controller was implemented on a two-link rehabilitation robot for gait training – the Lokomat®Pro V5 (Hocoma AG, Switzerland) and tested on 5 able-bodied subjects and 1 subject with Spinal Cord Injury. Our experiments show that the hybrid controller is a feasible approach for exoskeleton devices and that it could exploit the benefits of the end-point controller in shaping a desired end-point stiffness and those of the joint controller to guarantee the correct angular trajectories of the joints. The adaptation algorithm is able to adapt the end-point stiffness based on the subject’s performance in different gait phases, i.e. the robot can render a higher stiffness selectively in the direction and in the gait phases where the subjects perform the larger kinematic errors. The proposed approach can potentially be generalized to other robotic applications for rehabilitation or assistive purposes.